Leaving home: Technological and landscape knowledge as resilience at pre-Holocene Kharaneh IV, Azraq Basin, Jordan. (December 2022) - Macdonald, Danielle A; Maher, Lisa A
Humanity's relationship with the environment during the Holocene, and into the Anthropocene, is structured around our dependance on agricultural production, which has resulted in risk mitigation strategies that include intensive landscape modifications, among other tactics. However, to understand broader patterns of human resilience and the shifts in human/environment relationships, we need to look further back in time. Through this paper, we explore cultural strategies of risk management and resilience in pre-Holocene communities and how these practices allowed hunter-gatherer communities to adapt to a changing environment. For over 1000 years, the Epipalaeolithic site of Kharaneh IV was a focal point on the landscape for hunter-gatherer groups, acting as an aggregation site for Early and Middle Epipalaeolithic peoples. Located in the eastern desert of Jordan, at the time of occupation the site was a lush wetland surrounded by a rich grassland environment, providing abundant food and other resources for the site's occupants. However, over time the wetland began to dry up and by 18, 600 cal BP Kharaneh IV was abandoned. In this paper, we discuss the final occupation of Kharaneh IV, linking the site's abandonment to the increasing aridification of eastern Jordan. Environmental change led to the eventual abandonment of Kharaneh IV and other nearby sites, as people relocated within the Azraq Basin in search of new water resources during the Holocene. Flexible technological strategies and knowledge of the landscape created resilient cultural practices that allowed these communities to use population movement as a risk management strategy.